2020
DOI: 10.1021/acs.biochem.0c00736
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a Soluble meso-Tetraarylporphyrin to Human Galectin-7 Induces Oligomerization and Modulates Its Pro-Apoptotic Activity

Abstract: The selective targeting of protein–protein interactions remains a significant determinant for the proper modulation and regulation of cell apoptosis. Prototypic galectins such as human galectin-7 (GAL-7) are characterized by their ability to form homodimers that control the molecular fate of a cell by mediating subtle yet critical glycan-dependent interactions between pro- and anti-apoptotic molecular partners. Altering the structural architecture of GAL-7 can therefore result in resistance to apoptosis in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Galectins are known to induce apoptosis of human T cells by binding to their glycosylated receptors, thereby modulating cell fate in diseases such as cancer ( 42 ). For a number of years, our group has extensively used GAL-7 as a relevant model for studying Jurkat T cell induced apoptosis, providing additional information on molecular and cellular mechanisms governing GAL-7 function in the cell ( 11 , 14 , 34 , 43 ). Despite several studies detailing the existence of a homodimeric structure in GAL-7, few reports have thus far interrogated the importance of maintaining the integrity and stability of this dimer for preservation of function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Galectins are known to induce apoptosis of human T cells by binding to their glycosylated receptors, thereby modulating cell fate in diseases such as cancer ( 42 ). For a number of years, our group has extensively used GAL-7 as a relevant model for studying Jurkat T cell induced apoptosis, providing additional information on molecular and cellular mechanisms governing GAL-7 function in the cell ( 11 , 14 , 34 , 43 ). Despite several studies detailing the existence of a homodimeric structure in GAL-7, few reports have thus far interrogated the importance of maintaining the integrity and stability of this dimer for preservation of function.…”
Section: Resultsmentioning
confidence: 99%
“…This functional modulation further demonstrates the relevance of this protein–protein interaction as an efficient interface for future rational drug discovery programs targeting GAL-7. Indeed, many structurally homologous galectins are involved in mediating subtle yet critical glycan-dependent and -independent interactions between pro- and antiapoptotic molecular partners in the cell ( 15 , 33 , 43 ). As a result of their highly homologous GBS interactions, the specific targeting of selected galectin members remains one of the most promising avenues for future disease treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Given the multiple roles of galectins in controlling the tumor microenvironment, it is reasonable to hypothesize that the production and release of galectin-7 by cancer cells is one of multiple mechanisms used by GOF mutants of p53 to facilitate a protumorigenic microenvironment [40]. Such a role for galectin-7 in the tumor microenvironment would include its ability to induce local immunosuppression, as we know now that galectin-7, like many galectins, induces apoptosis in activated immune cells [37,41,42]. This role would also include the regulation of the expression of protumorigenic genes in cancer cells.…”
Section: De Novo Expression Of Galectin-7 By Mutated P53mentioning
confidence: 99%
“…A reduction in the ability of the protein to induce apoptosis of Jurkat T cells was observed [ 119 ]. More recently it was demonstrated that meso -tetrakis( p -sulfonatophenyl)porphyrin 27 (TpSPPH 2 , Figure 9 ) significantly reduced the level of (galectin-7-induced) apoptosis of human Jurkat T cells [ 120 ].…”
Section: Small-molecule Carbohydrate and Non-carbohydrate Galectin-7 Inhibitorsmentioning
confidence: 99%
“…Docking simulations on galectin-7 showed that the TpSPPH 2 moiety preferentially binds to three main subsites at the dimer interface. [ 120 ].…”
Section: Small-molecule Carbohydrate and Non-carbohydrate Galectin-7 Inhibitorsmentioning
confidence: 99%